DEMARKASI KONTEKS DUALISME SPESIFIK NATUR YESUS: EKSPOSISI YOHANES 5:19 - Yos Adoni Sesatonis Sesatonis; Stenly R. Paparang; Suwardi; Yuni Marsalina Boboy (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The dual nature of Jesus still leaves problems of interpretation and understanding. The emphasis on the humanity of Jesus is excessive, resulting in His divinity needing to be addressed in some aspects. On the other hand, overemphasizing the divinity of Jesus resulted in His humanity being hindered, especially in the aspect of His suffering and death. The text of John 5:19 is often misunderstood as if Jesus was not God because He could not do anything on His own. This has the potential to cause doctrinal deviations. This study uses a qualitative method with an exposition approach that looks at the basic texts of the dual nature of Jesus and summarizes the interpretation and understanding of the topic. From this approach, it can be seen several points of affirmation, namely: the specific dualism of the nature of Jesus is understood based on the demarcation of context, the motivation for interpretation and understanding is one of the first steps in understanding the demarcation of the dual nature of the context, and negative perceptions of understanding biblical Christology leading to logical misperceptions of the biblical internals.